The Art of the Real - Galerie Pierre Huber, Genève (Geneva : Galerie Pierre Huber, 1987)
Alexander, Vikky ; Brenner, Beth ; Corris, Michael ; Di Benedetto, Steve ; Eckart, Christian ; Hopkins, Peter ; Koons, Jeff ; McCaslin, Matthew ; McCollum, Allan ; Parrino, Steven ; Rollins & K.O.S., Tim ; Schuyff, Peter ; Stahl, Mark ; Wachtel, Julie ; Wallace & Donohue
The Art of the Real, Galerie Pierre Huber, Geneva, June - July 1987
boek